UDP-glucose dehydrogenase: structure and function of a potential drug target. - Egger, S; Chaikuad, A; Kavanagh, K; Oppermann, U; Nidetzky, B (2010)
Biosynthesis of the glycosaminoglycan precursor UDP-α-D-glucuronic acid occurs through a 2-fold oxidation of UDP-α-D-glucose that is catalysed by UGDH (UDP-α-D-glucose 6-dehydrogenase). Structure-function relationships for UGDH and proposals for the enzymatic reaction mechanism are reviewed in the present paper, and structure-based sequence comparison is used for subclassification of UGDH family members. The eukaryotic group of enzymes (UGDH-II) utilize an extended C-terminal domain for the formation of complex homohexameric assemblies. The comparably simpler oligomerization behaviour of the prokaryotic group of enzymes (UGDH-I), in which dimeric forms prevail, is traced back to the lack of relevant intersubunit contacts and trimmings within the C-terminal region. The active site of UGDH contains a highly conserved cysteine residue, which plays a key role in covalent catalysis. Elevated glycosaminoglycan formation is implicated in a variety of human diseases, including the progression of tumours. The inhibition of synthesis of UDP-α-D-glucuronic acid using UGDH antagonists might therefore be a useful strategy for therapy.